Policy options for climate policy in the residential building sector: The case of Germany - Sebastian Schröer (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
In order to achieve the climate protection goals in the building sector, a higher rate of building refurbishment is necessary to improve the energy standard of residential building stock in the European Union. Although subsidisation seems to be necessary, optimal measures concerning cost effectiveness are unclear. Using a stylised model of the German residential building stock, we analyse different refurbishment measures by simulating every relevant investment until 2030. In particular, we compare two different options that are relevant for political measures: first, comprehensive refurbishments that are expensive but achieve the greatest reductions in energy consumption and GHG emissions and second, partial refurbishments which include only low-cost improvements but can be achieved on a wide scale. We conclude that comprehensive refurbishments will require the least amount of investment costs per ton GHG emissions and provide the highest reductions in energy consumption in 2030. Hence, partial refurbishments are never optimal. However, in terms of cumulated GHG emissions in the period considered, the difference between both options is very small. This is due to their different dynamics: comprehensive refurbishments achieve fewer results in the first years but catch up quickly, which means that the higher the refurbishment rate the higher the advantage of comprehensive refurbishments.
Keywords: C60; H30; O33; Q40; Q58; 330; residential building sector; refurbishment; climate policy; energy saving; policy scenarios; Altbaumodernisierung; Energiesparen; Wohnimmobilien; Wirkungsanalyse; Prognose; Klimaschutz; Bauökologie; Deutschland